1997
DOI: 10.1093/humrep/12.7.1409
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged inhibition of normal ovarian cycles in the rat and cynomolgus monkeys following a single s.c. injection of danazol

Abstract: In castrated male rats, a single s.c. injection of danazol has been shown to result in an inordinately prolonged inhibition of serum luteinizing hormone (LH) and follicle stimulating hormone (FSH) concentrations. In the present study, we have examined whether the same and similar routes of administration suppresses ovarian function in normally cycling rats and cynomolgus monkeys. Normally cycling female rats received danazol as a single administration either orally, i.m. or s.c. and a separate group also recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Although one low‐dose female and one high‐dose female exhibited prolonged menstrual cycles, this was within the facility historical control range and thus was not considered ABT‐874‐related (Weinbauer et al., ). Furthermore, during the dosing period, ABT‐874‐dosed animals exhibited mean menstrual cycle lengths of 28 to 34 days, which is comparable to previously published ranges (Shaikh et al., ; Butterstein et al., ). This fact that the menstrual cycle was not adversely altered following administration of ABT‐874 is also consistent with a previously conducted study in IL‐12p40 knockout mice (Enright et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…Although one low‐dose female and one high‐dose female exhibited prolonged menstrual cycles, this was within the facility historical control range and thus was not considered ABT‐874‐related (Weinbauer et al., ). Furthermore, during the dosing period, ABT‐874‐dosed animals exhibited mean menstrual cycle lengths of 28 to 34 days, which is comparable to previously published ranges (Shaikh et al., ; Butterstein et al., ). This fact that the menstrual cycle was not adversely altered following administration of ABT‐874 is also consistent with a previously conducted study in IL‐12p40 knockout mice (Enright et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…Shaikh, Naqvi, and Shaikh (1978) observed a cycle duration of 29.2 days (range 22–37 days) in a total of 647 cycles. Butterstein et al (1997) reported an average cycle duration of 30.2 ± 1.4 (range 29–35) days. Another study on twenty individually housed cynomolgus monkeys reported a vaginal smear-based average cycle duration of 35.9 ± 1.6 days (range 26–45 days; Attia 1998).…”
Section: Ovarian Cyclementioning
confidence: 99%
“…There are a few reports showing that progestins are useful for control of ovulation in monkeys. Three out of 4 rhesus monkeys showed ovulation synchrony after daily administration of a progestin, altrenogest, mixed with fruit juice [8], and daily intramuscular injections with LNG [6] or a single subcutaneous injection with danazol [3] inhibited ovulation in cynomolgus monkeys. Although these studies suggested the possibility for that progestins control ovulation, the suitable doses and the effect of the treatment at different phases of the menstrual cycle on the time of ovulation had not been studied.…”
Section: Discussionmentioning
confidence: 97%
“…Daily intramuscular injection with a commonly used progestin contraceptive, levonorgestrel (LNG), inhibited follicular maturation and ovulation in cynomolgus monkeys [6]. A single subcutaneous administration of a synthetic progestogen, danazol, induced a prolonged suppression of ovarian cyclicity in cynomolgus monkeys [3]. Although these findings suggest that the use of progestogens is effective for control of ovulation in monkeys, suitable doses and effects of the treatment at different phases during the menstrual cycle had not been studied.…”
mentioning
confidence: 99%